Micronutrient value and contribution of plantainderivrd foods to daily intakes of iron, zinc and betacartene in southern Nigeria - Honfo, F.; Hell, K.; Coulibaly, O.; Tenkouano, A. (2007)
The present study aimed at determining the iron, zinc and β-carotene contents of the plantain-based foods commonly consumed in Southern Nigeria to assess the quantitative contribution of plantain consumption in meeting iron, zinc and vitamin A requirements of both children and their mothers. A survey was carried out in the Abia, Akwa-Ibom, Edo, and Ogun, States of Southern Nigeria, targeting their capital cities, i.e., Umuahia, Uyo, Benin City, and Abeokuta, respectively. In each state, sub-samples of 30 urban and 30 rural households were randomly taken, totalling 240 households. One third of each sub-sample of households had a child under 5 years old who was definitively weaned and whose mother was present in the household. Data collection was done in June and July 2005. The number of children consuming plantain chips and the daily amount consumed were higher in urban areas (P<0.05) than in rural areas. In both rural and urban zones, mothers' consumption levels were at least twice those of children. The iron content of all plantain products analysed ranged from 0.71 mg to 1.30 mg/100 g FW. It was higher in plantain chips than in fried plantain, which had the lowest iron content of all plantain products. The zinc content of the plantain-based foods analysed ranged from 0.24 mg to 0.37 mg/100 g FW. Unripe plantain and chips contained the highest levels of zinc. The β-carotene content was higher in plantain-based products (203.0-695.12 µg/100 g FW) compared to other staple foods, e.g. maize, cassava and yam, grown in Nigeria.